2012
DOI: 10.1108/14777831211232218
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable coastal zones? A matter of “sense and sensibility”

Abstract: Purpose-The purpose of this paper is to perform a comparative analysis between Aveiro's Lagoon (Portugal) and Sepetiba Bay (Brazil), in order to understand the similarities and differences between these two coastal zones, in terms of human occupation. Design/methodology/approach-This paper is supported by works (papers and scientific projects being developed) produced in Portugal and Brazil, by researchers from different areas of expertise. Findings-These two coastal zones have a similar geomorphologic evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The Aveiro region (Center of Portugal) is also being marked by different types of anthropogenic interventions, such as the Aveiro Port, several industries on the river and the lagoon margins such as the Estarreja Chemical Complex (Pereira et al, 1998;Bastos et al, 2012;Rodrigues et al, 2016). Biotic and sedimentological studies in the area showed enrichment of pollutants, such as Hg, Cr, Zn and Pb, in the surface sediments, both in the lagoon mouth and in the most confined areas (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The Aveiro region (Center of Portugal) is also being marked by different types of anthropogenic interventions, such as the Aveiro Port, several industries on the river and the lagoon margins such as the Estarreja Chemical Complex (Pereira et al, 1998;Bastos et al, 2012;Rodrigues et al, 2016). Biotic and sedimentological studies in the area showed enrichment of pollutants, such as Hg, Cr, Zn and Pb, in the surface sediments, both in the lagoon mouth and in the most confined areas (e.g.…”
Section: Introductionmentioning
confidence: 99%